2008
DOI: 10.1016/j.neuro.2008.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Manganese transport in eukaryotes: The role of DMT1

Abstract: Manganese (Mn) is a transition metal that is essential for normal cell growth and development, but is toxic at high concentrations. While Mn deficiency is uncommon in humans, Mn toxicity is known to be readily prevalent due to occupational overexposure in miners, smelters and possibly welders. Excessive exposure to Mn can cause Parkinson's disease-like syndrome; patients typically exhibit extrapyramidal symptoms that include tremor, rigidity and hypokinesia (Calne et al., 1994;Dobson et al., 2004).Mn-induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
195
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(200 citation statements)
references
References 81 publications
4
195
0
Order By: Relevance
“…Manganese exposure by itself has been shown to result in a variety of detrimental effects in C. elegans [146][147][148]. One study demonstrates that even short exposures (30 min) to manganese result in production of ROS, as evidenced by a drastic increase in glutathione levels [143].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese exposure by itself has been shown to result in a variety of detrimental effects in C. elegans [146][147][148]. One study demonstrates that even short exposures (30 min) to manganese result in production of ROS, as evidenced by a drastic increase in glutathione levels [143].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 99%
“…elegans studies have also confirmed that manganese exposure may have an additive effect on DAergic neurodegeneration in neurons containing α-synuclein protein aggregates. Various labs have concluded that the C. elegans SMF-1 transporter, an analogue of the divalent metal transporter (DMT-1) found in humans, is important in the degeneration of these neurons [146,147,149,150]. Results in C. elegans indicate that this transporter plays a significant role in neurotoxicity by transporting manganese into the cell where it can induce numerous intracellular changes.…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 99%
“…Being a paramagnetic substance, it reduces the spin-lattice relaxation time (T1) of surrounding water protons and, therefore, acts as a contrast agent in T1-weighted magnetic resonance (MR) images (Pautler et al, 1998, Saleem et al, 2002. When administered to the neural tissue, Mn 2+ enters neurons via different types of ion channels, including voltagegated calcium channels (Drapeau and Nachshen, 1984, Narita et al, 1990, Crossgrove and Yokel, 2005, as well as metal transporters, including divalent metal transporter 1 (DMT1) (Garrick et al, 2003, Au et al, 2008. Most importantly for neuroscientific studies, Mn 2+ is further transported by neural cells and can cross synapses (Sloot and Gramsbergen, 1994, Pautler et al, 1998, Saleem et al, 2002, which is not the case for all divalent metal ions (Tjalve et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Mn can reach the central nerve system (CNS) through DMT1 and/or TfR1 -mediated endocytosis (Diagram 3) [16,186]. Other transporters that can facilitate Mn entry to the CNS are store-operated and voltage-gated calcium channels [187,188], the choline transporter [189,190], citrate transporter [191] and ionotropic glutamate receptor Ca 2+ channels [192].…”
Section: Brain Transportmentioning
confidence: 99%
“…Within the brain, Mn binds to brain Tf which can mediate the neuronal uptake of Mn through TfR1 uptake mechanism that requires DMT1 for the metal export from the endosomes into the cytoplasm [15,186,199]. Also, DMT1 can facilitate Mn accumulation in DA-rich areas [200].…”
Section: Brain Transportmentioning
confidence: 99%